Determining the Effect of Orange Peel Extract in Water on Total Cholesterol Fluctuations in HFD-Induced Mice - Ria Qadariah Arief; Linda Prasetyaning W; Risa Purnamasari; Sarita Oktorina; Sri Hidayati L (State Islamic University of Sunan Ampel, 2023)
Hypercholesterolemia, characterized by elevated levels of total cholesterol, is a well-established risk factor for cardiovascular diseases, necessitating the exploration of natural interventions to mitigate dyslipidemia and its associated health risks. This study aimed to investigate the potential influence of orange peel extract in water on total cholesterol fluctuations in HFD-induced mice. This study used a true experimental design to investigate the effects of dietary interventions on total cholesterol levels in a female mice model. A total of 18 adult mice were utilized for this research, and they were divided into three distinct groups. The allocation of mice into these groups was as follows: Control Group (n=6): The first group served as the control and received only Aquades (sterile water). High-Fat Diet (HFD) Group (n=6) as named HFD only: The second group consisted of mice that were exclusively fed a high-fat diet (HFD) for a total of 17 days. Orange Peel Extract Group (n=6): The third group, also exposed to the HFD for an initial 10-day period, was subsequently administered orange peel extract for seven days. The total cholesterol levels of the mice that were given orange peel extract decreased from 109 ± 7.43 mg/dL to 96.5 ± 10.07 mg/dL after the intervention. This decrease was statistically significant (p < 0.05). the risk of high total cholesterol levels in mice that were given orange peel extract was 33.3%, compared to 83.3% in mice that were given aquades and 50% in mice that were still on a high-fat diet (HFD). , the results of this study suggest that orange peel extract may offer a natural and accessible approach to address dyslipidemia and reduce the risk of cardiovascular diseases. While further research is needed to confirm these findings and explore their applicability to human health.